Dendritic Cell-Lymphocyte Crosstalk Downregulates Host Restriction Factor SAMHD1 and Stimulates HIV-1 Replication in Dendritic Cells - Su, Bin (2014)
Human immunodeficiency virus type 1 (HIV-1) replication in dendritic cells (DCs) is restricted by SAMHD1. This factor is counteracted by the viral protein Vpx; Vpx is found in HIV-2 and simian immunodeficiency virus (SIV) from sooty mangabeys (SIVsm) or from macaques (SIVmac) but is absent from HIV-1. We previously observed that HIV-1 replication in immature DCs is stimulated by cocultivation with primary T and B lymphocytes, suggesting that HIV-1 restriction in DCs may be overcome under coculture conditions. Here, we aimed to decipher the mechanism of SAMHD1-mediated restriction in DC-lymphocyte coculture. We found that coculture with lymphocytes downregulated SAMHD1 expression and was associated with increased HIV-1 replication in DCs. Moreover, in infected DC-T lymphocyte cocultures, DCs acquired maturation status and secreted type 1 interferon (alpha interferon [IFN-α]). The blockade of DC-lymphocyte cross talk by anti-ICAM-1 antibody markedly inhibited the stimulation of HIV-1 replication and prevented the downregulation of SAMHD1 expression in cocultured DCs. These results demonstrate that, in contrast to purified DCs, cross talk with lymphocytes downregulates SAMHD1 expression in DCs, triggering HIV-1 replication and an antiviral immune response. Therefore, HIV-1 replication and immune sensing by DCs should be investigated in more physiologically relevant models of DC/lymphocyte coculture.